SYSTEM DESIGN AND BEHAVIOR OF PATTERN RECOGNITION OF CONTROL CHART USING NEURAL NETWORK - Justin Yulius Halim (Institute of Research and Community Outreach - Petra Christian University, 2003)
Recognition of unnatural patterns in control charts is important to get more understanding about the process problem. Shewhart control chart can recognize shift pattern only, while the others cannot be detected by this chart. Neural networks were proposed by many researchers to achieve the better recognition of the patterns. A system of neural networks needs to be fitted to this problem by realizing the behaviors of control charts. Each behavior will affect the development of each part of the system. Some problem need to be pointed also when dealing with the patterns of the control chart.